Microbial Diversity and Community Structures Among Those With Moderate to Severe TBI: A United States-Veteran Microbiome Project Study. Issue 5 (September 2020) - Brenner, Lisa A.; Stamper, Christopher E.; Hoisington, Andrew J.; Stearns-Yoder, Kelly A.; Stanislawksi, Maggie A.; Brostow, Diana P.; Hoffmire, Claire A.; Forster, Jeri E.; Schneider, Alexandra L.; Postolache, Teodor T.; Lowry, Christopher A.
Abstract : Objective: To evaluate the association between distal moderate/severe traumatic brain injury (TBI) history and the human gut microbiome. Setting: Veterans Affairs Medical Center. Participants: Veterans from the United States-Veteran Microbiome Project (US-VMP). Veterans with moderate/severe TBI ( n = 34) were compared with (1) Veterans with a history of no TBI ( n = 79) and (2) Veterans with a history of no TBI or mild TBI only ( n = 297). Design: Microbiome analyses from 16S rRNA gene sequencing with gut microbiota function inferred using PICRUSt2. Main Measures: α-Diversity and β-diversity of the gut microbiome, as well as taxonomic and functional signatures associated with moderate/severe TBI. Results: There were no significant differences in gut bacterial α- and β-diversity associated with moderate/severe TBI status. No differentially abundant taxa were identified when comparing samples from moderate/severe TBI to those with no TBI or no TBI/mild TBI. Conclusion: Results suggest that moderate/severe TBI-related changes to the gut microbiome do not persist for years postinjury. Abstract : Supplemental Digital Content is Available in the Text.